The effect of scheduling a drill to teach some basic offensive skills Basketball Experimental research on female first-stage students at the College of Physical Education for Girls For the academic year 2005-2006 (Journal of the College of Basic Education, 2023)
There have been many developments in the fields of learning and education and on the theoretical and practical levels as a result of the experiments reached by the researchers, and despite that, scientific experiments and research are still continuing to achieve the best educational means and methods that contribute to the development of the education process according to the theories and concepts of motor learning and its scientific applications. It is one of the complex operations, because it contains principles and concepts that are constantly changing in the light of the variables of the environment, the learner, the possibilities, the types of skills, and their classification, which makes it difficult to plan the educational units.The researcher assumed that there is a discrepancy between the methods of organizing exercises, and there are also differences in the use of methods of organizing exercises to learn some basic offensive skills in basketball between the pre and post tests.The experimental approach was used to achieve the goal of imposing the research on a sample of 75 female students divided into five groups, with (15) female students per group.I used the appropriate statistical methods, which achieved what the research aims for, and it was concluded:• There is a clear significant difference in the effect on learning and for all five groups on technical performance, accuracy and speed.• It appeared that the best nested learning method (random - variable) in teaching technical performance and its speed for my skill (handling - tapping).